Ausencia de gestión como factor en las adquisiciones y compras del sector de la construcción en la ciudad de Cartagena D.T. y C. - Tous Hernández, Jairo Arturo (Arquitectura, Arte y Diseño, 2019)
Currently, the organizations are focused on the search to plan and execute successful projects and improve the expectations stipulated by investors in the construction sector. The Acquisitions and Purchasing processes are constituted within the administrative scale to execute works of great amplitude, contributing strategic leadership, within the policies that guarantee to reduce gradually the setbacks and errors of delays in the final deliveries of a work. Identifying and generating quality is today one of the great challenges that covers, to a large extent, objectives, operational plans, optimization of resources and budgets; Detecting future unforeseen events, shortcomings and costs in Colombia, exactly in the city of Cartagena de Indias, where engineering, horizontal property, mega constructions, industrial plants, camps, ports and others prevail. In this reflective and descriptive article, an analysis is made related to the behavior of the procurement and purchasing area, taking as examples of recurrent and real cases in the construction sector that have generated the same results due to lack of management